Ruotsissa kartoitetaan ilmastomallilla alkukasvukauden hallariskejä - Poteri, Marja (Metsäntutkimuslaitos, 2011)
Selostus atikkelista: Langvall, O. 2011. Impact of climate change, seedling type and provenance on the risk of damage to Norway spruce (Picea abies (L.) Karst.) seedlings in Sweden due to early summer frosts. Scandinavian Journal of Forest Research 26(S11): 56–63.
Julkaisusatoa
Keywords: kuusen viljely; taimituhot